KESESUAIAN PENGKAJIAN RESEP RACIKAN PEDIATRI DI RSUD SIWA - Aztriana, Aztriana; Mumtihanah, Andi; Kadir, Melly Amanda (Makassar Pharmaceutical Science Journal (MPSJ), 2023)
After receiving a prescription, it is the responsibility of a pharmacist to examine the prescription's administrative, pharmacological, and clinical components for completeness, suitability, and accuracy. This study aimed to examine the administrative, pharmacological, and clinical completeness of pediatric prescriptions at RSUD of Siwa pertinent to Minister of Health Regulation No. 72 of 2016 concerning Pharmaceutical Service Standards in Hospitals. This research was conducted at RSUD of Siwa Hospital using descriptive quantitative methodology. During the period of October to December 2021, 104 pediatric prescription sheets were collected retrospectively using the approach of purposive sampling, and 51 prescription sheets matched the inclusion criteria and data processing was then performed based on the completeness of administrative aspect, the suitability of pharmaceutical aspect and the clinical aspect. The results obtained on administrative aspect were as comprehensive as 67.91%, pharmacological aspects as comprehensive as 80%, clinical aspect of the drug interaction component as complete as 45%, and dosage accuracy as complete as 31,38%.